2009
DOI: 10.1111/j.1601-5223.1973.tb01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between marker genes on barley chromosome 2 and a gene for resistance to Heterodera avenae

Abstract: A close linkage is shown in barley between a gene for resistance to race 1 and 2 of Heterodera avenae (Ha2) and lack of purple colour at nodes, ligules and awns (pau). A number of recombination values between genes are given and a likely order is suggested for the following genes: Ha2, pau, cer gl0, v and e, and the translocation break T,-,f. A survey is given of the varieties used and the problems encountered are briefly outlined. The importance for plant breeding is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The seeds of eight barley (Hordeum vulgare) cultivars, Skiff, Schooner, Sloop, Sloop SA (Rha2), Sloop VIC (Rha2), Galleon (Rha4), Chebec (Rha2) and Dash (resistant but not known to carry either Rha2 or Rha4), were provided by Stewart Coventry (University of Adelaide, Australia). In previous work, Kretschmer et al (1997) concluded that the resistance locus in Chebec was Rha2 (Cotten & Hayes, 1969;Andersen & Andersen, 1973). A similar locus was mapped in Sahara 3771.…”
Section: Plant Materialsmentioning
confidence: 81%
See 2 more Smart Citations
“…The seeds of eight barley (Hordeum vulgare) cultivars, Skiff, Schooner, Sloop, Sloop SA (Rha2), Sloop VIC (Rha2), Galleon (Rha4), Chebec (Rha2) and Dash (resistant but not known to carry either Rha2 or Rha4), were provided by Stewart Coventry (University of Adelaide, Australia). In previous work, Kretschmer et al (1997) concluded that the resistance locus in Chebec was Rha2 (Cotten & Hayes, 1969;Andersen & Andersen, 1973). A similar locus was mapped in Sahara 3771.…”
Section: Plant Materialsmentioning
confidence: 81%
“…In previous work, Kretschmer et al . () concluded that the resistance locus in Chebec was Rha2 (Cotten & Hayes, ; Andersen & Andersen, ). A similar locus was mapped in Sahara 3771.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In barley, the inheritance of CCN resistance was first investigated by Nilsson-Ehle ( 1920 ), who reported results indicating segregation of a single unit of inheritance, for which resistance was dominant. Subsequent research established that there are up to three CCN resistance loci on chromosome 2H (Andersen and Andersen 1968 , 1973 ; Cotten and Hayes 1969 ; Kretschmer et al 1997 ). Of these, two (originally called Ha2 and Ha3 but now called Rha2 and Rha3 ) are very closely linked with each other (or may even be the same locus).…”
Section: Introductionmentioning
confidence: 99%
“…Especially interesting is the Ha2 ‐gene which confers resistance to H. avenae race 1 and 2 (Andersen and Andersen 1973). The selection of resistant genotypes relies on the count of cysts infesting the roots of plants, a simple but laborious and thus expensive bioassay (Andersen and Andersen 1973). Ha2 ‐linked restriction fragment length polymorphism (RFLP) markers have been developed (Kretschmer et al.…”
mentioning
confidence: 99%